2020
DOI: 10.1111/2041-210x.13456
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐portable solar power to facilitate continuous operation of technology in the field

Abstract: Electronic devices are frequently used for field ecological research (e.g. Allan et al., 2018; Marvin et al., 2016). In many cases these devices are left in the field for weeks or months at a time. For example, passive acoustic monitoring devices (e.g. Wildlife Acoustics) are designed to continuously record soundscapes for months; trail cameras have opened a new realm of animal research (O'Connell, Nichols, & Karanth, 2010), and the use of radio frequency identification (RFID) to track movement and behaviour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It is also possible to run the Raspberry Pi on solar energy. A small 5 V 6 W solar panel can suffice for the most basic requirements, and larger, more permanent systems can be an ideal solution for many field systems, such as including a 12 V/18 V 50 W solar panel, a solar charger and a 12 V battery (see Proppe et al., 2020; Sethi et al., 2018).…”
Section: Guidelines Pointers and Considerations For Implementing The ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to run the Raspberry Pi on solar energy. A small 5 V 6 W solar panel can suffice for the most basic requirements, and larger, more permanent systems can be an ideal solution for many field systems, such as including a 12 V/18 V 50 W solar panel, a solar charger and a 12 V battery (see Proppe et al., 2020; Sethi et al., 2018).…”
Section: Guidelines Pointers and Considerations For Implementing The ...mentioning
confidence: 99%
“…For example, when there is 5 hr of expected sun per day, the system should be able to run 3 days without any sun, and energy efficiency is 70%, then the solar panel should be at least 6 W ((0.35 A × 3 hr × 5 V) × 4 day/0.7/5). Real‐life power consumption tests with your system are recommended before putting it to use (see Proppe et al., 2020 for further information).…”
Section: Guidelines Pointers and Considerations For Implementing The ...mentioning
confidence: 99%
“…In a battery-powered configuration utilizing the RPi 3B+ with an average current draw of 528 mA from a 5 V source, the operational power demand of the system is approximately 2.64 W. Employing a 50 Ah commercial power bank as the energy reserve, the effective output is calculated to be 250 Wh (50 Ah × 5 V), projecting the operational longevity of our edge device on this power supply to be around 94 h (250/2.64). Considering the variable nature of CPU usage, a conservative estimate adjusts the expected battery life to 50% of this duration [69], translating to an operational range between 47 and 94 h without the need for manual intervention. Previous work [70] has shown that integrating an RPi with a 12 V 50 W solar panel with a solar charger and a 12 V battery can facilitate continuous operation in the field, devoid of frequent maintenance needs.…”
Section: Edge Device Analysismentioning
confidence: 99%
“…Using S-MLS with solar power energy the cost will be zero in all three locations. Proppe et al (2020) stated that the solar recharge rate depends on the consistency of the sunlight. Sunlight can harvest with a maximum of 4-6 hours of direct peak.…”
Section: Research Questionmentioning
confidence: 99%